The expression of type III hyperlipoproteinemia: involvement of lipolysis genes - Henneman, Peter (Nature Publishing Group, 2009)
Type III hyperlipoproteinemia (HLP) is mainly found in homozygous apolipoprotein (APO) E2 (R158C) carriers. Genetic factors contributing to the expression of type III HLP were investigated in 113 hyper- and 52 normolipidemic E2/2 subjects, by testing for polymorphisms in APOC3, APOA5, HL (hepatic lipase) and LPL (lipoprotein lipase) genes. In addition, 188 normolipidemic Dutch control panels (NDCP) and 141 hypertriglyceridemic (HTG) patients were genotyped as well. No associations were found for four HL gene polymorphisms and two LPL gene polymorphisms and type III HLP. The frequency of the rare allele of APOC3 3238 G>C and APOA5 −1131 T>C (in linkage disequilibrium) was significantly higher in type III HLP patients when compared with normolipidemic E2/2 subjects, 15.6 vs 6.9% and 15.1 vs 5.8%, respectively, (P<0.05). Furthermore, the frequencies of the APOA5 c.56 G>C polymorphism and LPL c.27 G>A mutation were higher in type III HLP patients, though not significant. Some 58% of the type III HLP patients carried either the APOA5 −1131 T>C, c.56 G>C and/or LPL c.27 G>A mutation as compared to 27% of the normolipidemic APOE2/2 subjects (odds ratio 3.7, 95% confidence interval=1.8–7.5, P<0.0001). The HTG patients showed similar allele frequencies of the APOA5, APOC3 and LPL polymorphisms, whereas the NDCP showed similar allele frequencies as the normolipidemic APOE2/2. Patients with the APOC3 3238 G>C/APOA5 −1131 T>C polymorphism showed a more severe hyperlipidemia than patients without this polymorphism. Polymorphisms in lipolysis genes associate with the expression and severity of type III HLP in APOE2/2.